Fetal echocardiography in uncommon parental cardiac anomalies: right atrium diverticulum, interventricular septal aneurysm, left and right ventricle diverticulum - report from referral center for fetal cardiology in Poland - Płużańska, Joanna; Respondek-Liberska, Maria (Prenatal Cardiology, 2018)
The prenatal detection of congenital anomalies of heart walls is very rare. We present a unique series of 8 cases with prenatal echocardiographic monitoring, treatment and postnatal follow-up, providing new insight into this “mysterious” heart problem.